2022
DOI: 10.1177/1934578x211029522
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Is a Promising Alkaloid to Attenuate Iron Toxicity Efficiently in Iron-Overloaded Mice

Abstract: Iron toxicity in iron-overloaded conditions, including high iron diet and blood transfusion, causes deleterious effects on vital organs. There currently are a number of chemical chelators in clinics to reduce iron concentration, for example , deferoxamine and deferiprone, but these produce diverse side effects. Hence, the need for a safe and effective iron chelator is demanded. To evaluate rigorously the potential of berberine on iron chelation and its anti-oxidant effect, 30 mice were divided into 5 groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…FA and CaA increased CAT activity in the brain, liver, and serum of the treatment mice (Figures 6A-C). Previous studies have shown that the antioxidant enzyme activity was affected by iron overload; and natural products and DFO increased the antioxidant enzyme activity (2,40,41).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…FA and CaA increased CAT activity in the brain, liver, and serum of the treatment mice (Figures 6A-C). Previous studies have shown that the antioxidant enzyme activity was affected by iron overload; and natural products and DFO increased the antioxidant enzyme activity (2,40,41).…”
Section: Discussionmentioning
confidence: 93%
“…Due to the negative effects of DFO, the use of natural compounds as iron chelators is justified. Other studies have shown some natural products, such as CaA, FA, Berberine, and Vanillic acid, reduced iron content in the heart or liver significantly (2,(40)(41)(42). Resveratrol reduces oxidative stress in the brains of treated rats (43).…”
Section: Discussionmentioning
confidence: 94%
“…An in vivo study on iron-overloaded mice by Aalikhani et al showed that berberine decreased total iron levels in the liver, kidney, and lung tissues. Berberine prevents lipid peroxidation by reducing excess iron and chelating it in tissues, which is equivalent to DFO, an iron-chelating drug [ 181 ].…”
Section: Antioxidant Activity Of Berberinementioning
confidence: 99%